2014
DOI: 10.1021/ml4002503
|View full text |Cite
|
Sign up to set email alerts
|

Analogues of the Natural Product Sinefungin as Inhibitors of EHMT1 and EHMT2

Abstract: A series of analogues of the natural product sinefungin lacking the amino acid moiety was synthesized and probed for their ability to inhibit EHMT1 and EHMT2. This study led to inhibitors 3b and 4d of methyltransferase activity of EHMT1 and EHMT2 and it demonstrates that such analogues constitute an interesting scaffold to develop selective methyltransferase inhibitors. Surprisingly, the inhibition was not competitive toward AdoMet. KEYWORDS: Sinefungin, methyltransferase inhibitors, EHMT1, EHMT2 H istone modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Sinefungin is an AdoMet analogue containing an aminomethylene group in place of the methylated sulfonium group that typically acts as the methyl donor. It competes with AdoMet for MTase-binding and thereby inhibits AdoMet-dependent MTases in a non-selective manner [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sinefungin is an AdoMet analogue containing an aminomethylene group in place of the methylated sulfonium group that typically acts as the methyl donor. It competes with AdoMet for MTase-binding and thereby inhibits AdoMet-dependent MTases in a non-selective manner [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Currently known inhibitors of SET‐domain histone methyltransferases function as either competitive inhibitors of the substrate peptides or inhibitors of the cofactor AdoMet. For example, compounds such as BIX01294, E72, and UNC0321 have been found to block binding of the target peptide of H3 to the histone methyltransferase G9a, and Sinefungin derivatives have been developed that bind in place of AdoMet . Targeting histone methyltransferases via these mechanisms may be potentially difficult because of the need to develop specific inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, compounds such as BIX01294, E72, and UNC0321 have been found to block binding of the target peptide of H3 to the histone methyltransferase G9a, and Sinefungin derivatives have been developed that bind in place of Ado-Met. 12,[20][21][22][23] Targeting histone methyltransferases via these mechanisms may be potentially difficult because of the need to develop specific inhibitors. Indeed, Nguyen et al have studied the binding site similarity of SET-domain methyltransferases and found scaffolds that may bind to subsets of these.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although the conformation of bound SAM cofactor is very similar across different SET domains due to a precise hydrogen bond network, SAM-binding pockets contain enough structural diversity surrounding this network to allow development of specific inhibitors for different KMTases [135]. Indeed, chemical modification of SAM or closely related compounds such as sinefungin has led to potent and specific inhibitors for future science group Review Rogawski, Grembecka & Cierpicki several KMTases [122,136,137]. An additional consideration for designing SAM-derivative inhibitors is that the SAM-binding pocket is immediately adjacent to the narrow substrate lysine-binding channel.…”
Section: Post-setmentioning
confidence: 99%